Peningkatan Kapasitas Akademik Melalui Model Pelatihan Terstruktur Pada Workshop Penulisan Artikel Ilmiah Terakreditasi SINTA 2 dan SINTA 4 - Ginting, Reza Pahlevi; Retno, Sujacka; Trisfayani, Trisfayani; Mahsa, Masithah; Safriandi, Safriandi; Maghfirah, Riezka (Penerbit Widina, Widina Media Utama, 2025)
This community service program was designed to enhance the academic writing capacity of lecturers, teachers, and students in preparing scientific articles eligible for publication in SINTA 2 and 4 accredited journals. In response to the increasing demand for scientific publications as part of academic performance and graduation requirements in Indonesia, this initiative aimed to address common challenges such as lack of writing skills, limited understanding of journal requirements, and low confidence in submitting to reputable journals. The program adopted the Participatory Action Research (PAR) approach, which encourages the active participation of stakeholders in identifying problems, implementing solutions, and reflecting on outcomes. The workshop was held online and structured in three main phases: preparation, implementation, and evaluation. Preparation involved needs assessment and module development. The implementation phase included material delivery, interactive sharing sessions with experienced journal reviewers, and practical writing exercises. Participants also engaged in a simulated manuscript submission process using the Open Journal System (OJS). A total of 40 participants comprising lecturers, teachers, and students from the Universitas Malikussaleh area took part in the one-day intensive workshop. Evaluation results indicated a significant improvement in participants' knowledge and skills, with post-test scores rising and 92% reporting satisfaction, particularly with the practice-based sessions and direct feedback from facilitators. This program demonstrated that a structured, practical, and participatory training model could effectively build scientific writing competence. The integration of technical tools and active mentorship was key to bridging the gap between understanding and actual implementation. The program not only improved participants’ confidence but also contributed to strengthening the culture of scientific publication among academic communities in regional Indonesia.ABSTRAKProgram pengabdian kepada masyarakat ini dirancang untuk meningkatkan kapasitas menulis ilmiah dosen, guru, dan mahasiswa dalam menyusun artikel yang layak dipublikasikan pada jurnal terakreditasi SINTA 2 dan 4. Kegiatan ini merupakan respons terhadap meningkatnya tuntutan publikasi ilmiah sebagai bagian dari penilaian kinerja akademik dan syarat kelulusan di Indonesia. Program ini sekaligus menjadi solusi atas berbagai kendala umum seperti keterbatasan kemampuan menulis, kurangnya pemahaman terhadap ketentuan jurnal, serta rendahnya kepercayaan diri untuk mengirim artikel ke jurnal bereputasi. Kegiatan dilaksanakan dengan menggunakan pendekatan Participatory Action Research (PAR) yang mendorong keterlibatan aktif peserta dalam mengidentifikasi masalah, melaksanakan solusi, dan melakukan refleksi terhadap hasil. Workshop dilakukan secara daring dan terbagi dalam tiga tahap utama: persiapan, pelaksanaan, dan evaluasi. Tahap persiapan meliputi analisis kebutuhan dan penyusunan modul. Tahap pelaksanaan mencakup penyampaian materi, sesi berbagi pengalaman bersama reviewer jurnal, serta praktik penulisan artikel. Peserta juga mengikuti simulasi proses submit naskah melalui sistem Open Journal System (OJS). Sebanyak 40 peserta yang terdiri dari dosen, guru, dan mahasiswa di wilayah Universitas Malikussaleh mengikuti workshop intensif selama satu hari. Hasil evaluasi menunjukkan peningkatan signifikan pada pemahaman dan keterampilan menulis peserta. Skor post-test meningkat, dan 92% peserta menyatakan puas, terutama pada sesi praktik dan pendampingan langsung. Program ini membuktikan bahwa model pelatihan terstruktur dan partisipatif dapat secara efektif membangun kompetensi penulisan ilmiah serta memperkuat budaya publikasi di kalangan akademisi daerah.